Synthesis of Catalyst Cobalt Impregnated on Activated Natural Zeolite, Co/ANZ - Tri Kurnia Dewi; Zainal Fanani (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2017)
Research has been done on the synthesis of catalyst Co/Activated Natural Zeolite. The variables studied were the mass ratio of Cobalt to Zeolite and temperature of reduction during catalyst activation. The catalyst produced were analysed in their acidity and surface area. Acidity was presented in the form of ammonia and pyridine adsorption on the catalyst surface. The results showed the increasing Cobalt to Zeolite mass ratio will increase acidity of the catalyst produced. Reduction temperature during catalyst activation also gave same effect as Cobalt to Zeolite mass ratio did. Best ratio within the range of this study was Cobalt to Zeolite mass ratio of 6:20, which was found at reduction temperature of 400 C. This ratio gave catalyst acidity correspond to ammonia adsorption of 6.4615 mmol/g, and to pyridine adsorption of 2.6047 mmol/g catalyst. The best reduction temperature was 450 C at ratio of 6:20. The acidity of this catalyst was of 7.5202 mmol/g as in ammonia adsorption, and was of  3.662 mmol/g as in pyridine adsorption. Catalyst surface area of the best ratio was 32.63 m2/g, whilst catalyst surface area of the best reduction temperature was 38.95 m2/g. Keywords: catalyst, cobalt, activated natural Zeolite